2000
DOI: 10.1590/s0100-879x2000000500010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of 25 children and adolescents with severe aplastic anemia treated with antithymocyte globulin

Abstract: Severe aplastic anemia (SAA) is probably an immune-mediated disor-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Other studies have shown that the curative eVect of treatment combined with IST could be increased with increased treatment time. The overall response rates in months 3, 6, and 12 were 61, 74, and 86%, respectively, the long-term survival rate could reach 86%, and the relapse rate decreased to less than 10% (Führer et al 1998;De-Medeiros et al 2000). The treatment h-ATG is used in most countries but r-ATG is rarely used.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the curative eVect of treatment combined with IST could be increased with increased treatment time. The overall response rates in months 3, 6, and 12 were 61, 74, and 86%, respectively, the long-term survival rate could reach 86%, and the relapse rate decreased to less than 10% (Führer et al 1998;De-Medeiros et al 2000). The treatment h-ATG is used in most countries but r-ATG is rarely used.…”
Section: Discussionmentioning
confidence: 99%
“…A toxicidade se tornou aceitável e os resultados melhoraram, atingindo em torno de 70% de sobrevida e a rejeição não ocorreu em 50 pacientes transplantados, num período de 10 anos (32) . A experiência desenvolvida em Curitiba foi distinta (33,34,35) , pois procuramos, sem o uso da irradiação, encontrar a dose ideal de ciclofosfamida. Assim, reduzimos progressivamente a dose deste agente, obtendo sobrevidas prolongadas cada vez maiores, e hoje estamos utilizando 60 mg/kg com uma toxicidade praticamente circunscrita às mucosas e sobrevida perto de 100%.…”
Section: Anemia De Fanconiunclassified